Upconversion properties of the Er-doped Y2o3, Bi2o3 and Sb2o3 nanoparticles fabricated by pulsed laser ablation in liquid media - Zamiri, Reza; Bahari Poor, Hamid Reza; Zakaria, Azmi; Jorf, Raheleh; Zamiri, Golnoush; Rebelo, Avito; Omar, Akrajas Ali (Institute of Physics Publishing, 2013)
Er-doped Y2O3, Bi2O3 and Sb2O3 nanoparticles are synthesized using pulsed laser ablation in a liquid. Ceramic targets of Y2O3:Er3+, Bi2O3:Er3+ and Sb2O3:Er3+ for ablation process are prepared by standard solid-state reaction technique and ablation is carried out in 5-ml distilled water using nanosecond Q-switched Nd:YAG laser. The morphology and size of the fabricated nanoparticles are evaluated by transmission electron microscopy and the luminescence emission properties of the prepared samples are investigated under different excitation wavelengths.